EKSISTENSI MUSIK KERONCONG DALAM KEHIDUPAN MASYARAKAT JAWA DI KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrak: The spread of Keroncong music to various cities in the coastal areas ofIndonesia gives the local characteristics of its music in the distribution area. It spreadsbeyond the island of Java and gives birth to its distinctive features. However, manyassumed that Keroconcong Music is the same across Indonesia, originated in Jakarta,specifically in the Tugu Jakarta area. This study aimed to investigate the development,existence, community views and values of Keroncong music in the Rengat sub-districtarea. This study uses qualitative research methods to accurately describe, investigateand analyze the development and existence of Keroncong music in the Rengat subdistrictarea. Data analysis techniques used were data reduction, data presentation,verifications and concluding. The results of this research show that people in Rengatdistrict preserve the existence of Keroncong Music by first combining Malaysian songsand millennium songs with Keroncong music and spreading the moral value inKeroncong Music in daily life and society.Key Words: Existence, Music, Keroncong, Rengat Society.